PENGGUNAAN MODEL PEER TEACHING (TUTOR SEBAYA) Dalam Pembelajaran Pendidikan Agama Islam Pada Kurikulum Merdeka Belajar di SMKN 1 IV Koto Aur Malintang - Nafsiyati, Hilma; Amirah, Nurul (Mau`izhah : Jurnal Kajian Keislaman, 2023)
The purpose of the study, to describe the use of learning peer teaching, syntax, social systems, and reaction principles in the use of , Islamic Religious Education learning moodles. This type of research is field research using a descriptive approach. The results of the research presented from this study are the first syntax m odel peer teaching, namely educators choose material to be studied independently, and the material is divided into sub-sub material (material segments), dividing students into small groups as many as the sub-sub material that has been delivered teacher, Determine a tutor in each group, given the task of studying sub material, assisted by students who become tutors, After all groups complete their tasks, give conclusions and clarifications. The second Social System of the Peer Teaching Model, educators are in charge of providing material in the classroom, selecting tutors, dividing groups, namely supervising / controlling the extent to which students do the Peer Tutor Model, evaluating after using the Peer Tutor Model. Educators evaluate by giving exams/tests, conducted at the end of each month. The third Principle of Reaction to the Peer Teaching Model is that students find learning very fun, full of challenges and they feel excited.